analysis of Product Integration Methods for a Class of Singular Volterra Integral Equations - Diogo, T.; Lima, P.; Franco, N.B. (Trends in Computational and Applied Mathematics, 2000)
The construction and analysis of high order numerical methods for Volterra integral equations with a certain weakly singular kernel have been investigated in [6], under the assumption the the solution is sufficiently smooth.